2012
DOI: 10.1111/apha.12026
|View full text |Cite
|
Sign up to set email alerts
|

Renal pericytes: regulators of medullary blood flow

Abstract: Regulation of medullary blood flow (MBF) is essential in maintaining normal kidney function. Blood flow to the medulla is supplied by the descending vasa recta (DVR), which arise from the efferent arterioles of juxtamedullary glomeruli. DVR are composed of a continuous endothelium, intercalated with smooth muscle-like cells called pericytes. Pericytes have been shown to alter the diameter of isolated and in situ DVR in response to vasoactive stimuli that are transmitted via a network of autocrine and paracrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 131 publications
(312 reference statements)
0
58
0
Order By: Relevance
“…Vascular resistance in kidneys of L‐NAME–treated rats was greater in the medulla than in the cortex, which was caused by a shift of intrarenal blood flow and hence oxygen delivery from medulla to cortex 49. Arterioles of juxtamedullary glomeruli, which provide blood flow to the medulla, contain more smooth muscle than those of glomeruli in the cortex 50, 51. Consequently, blood supply to the medulla is more dependent on the NO vasodilatory reserve than the cortex 52.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular resistance in kidneys of L‐NAME–treated rats was greater in the medulla than in the cortex, which was caused by a shift of intrarenal blood flow and hence oxygen delivery from medulla to cortex 49. Arterioles of juxtamedullary glomeruli, which provide blood flow to the medulla, contain more smooth muscle than those of glomeruli in the cortex 50, 51. Consequently, blood supply to the medulla is more dependent on the NO vasodilatory reserve than the cortex 52.…”
Section: Discussionmentioning
confidence: 99%
“…Cross talk of free radicals between cells and neighboring tissues has been the subject of much interest and controversy. Although it remains unclear how sufficient amounts of O 2 ·Ϫ , H 2 O 2 , or NO could be released from mTAL epithelial cells and escape enzymatic degradation or interactions with other oxidizing molecules, there is compelling experimental evidence that this can occur under certain conditions (32,90,132,140). Using freshly isolated thin tissue strips from the inner stripe of the outer medulla and time-resolved fluorescence videomicroscopy techniques, it was found that mTAL of SS rats exhibited greater rates of O 2 ·Ϫ production in response to ANG II stimulation compared with SS.…”
Section: Excess O 2 ·ϫ and H 2 O 2 Production Relative To No In Mtal mentioning
confidence: 99%
“…Kidney pericytes regulate renal blood flow 6 and are emerging key players in the development of renal fibrosis and chronic kidney disease (CKD). Pericytes contribute to the renal myofibroblast pool in renal fibrogenesis via pericyte–myofibroblast trans-differentiation, and their detachment of capillaries might trigger capillary rarefaction, one of the hallmarks of acute kidney injury to CKD progression.…”
mentioning
confidence: 99%